Landscape, place and identity: the castles of the Holderness Plain, East Yorkshire. (2nd January 2021) - Jamieson, Elaine
ABSTRACT: This paper explores the importance of landscape and place in the creation of identity and the establishment of power in the period following the Norman Conquest. It focuses on the Holderness Plain, in the East Riding of Yorkshire, and takes the view that the character of the landscape points towards a region which retained an enduring sense of place. It examines the nature and spatial dimension of lordship in Holderness in the period immediately following the Norman Conquest. Focusing on the medieval castles of the Plain, it explores the role of ancient monuments, natural places and existing systems of authority in the establishment of new centres of power. Through a detailed case study of Skipsea castle, it considers the ways in which the natural and cultural landscape shaped the form and siting of the Norman fortress, and how this elite centre changed through time. It also sheds new light on the ways in which the development of Skipsea castle influenced the surrounding settlement pattern, revealing how the castle and wider changes to social and cultural practices impacted on the people who inhabited the land. The conclusion is that the Norman aristocracy were drawing on the texture of the landscape and the memories and traditions of local communities as a means of reinforcing power and control.